PREHISPANIC OCCUPATION IN SAN PEDRO DE LARCAY DISTRICT, SUCRE - AYACUCHO - Mallco Huarcaya, Rafael (2012)
The different works of archaeological exploration carried out in the area from the district of San Pedro de Larcay, province Sucre, department of Ayacucho, they have allowed to identify numerous archaeological sites that correspond to different cultures that were developed in this part of Peru. The archaeological evidences belong to societies that were developed as of the Period Average Horizon until the Inka time. Nevertheless, the presence of other sites with earlier occupation does not discard, since in the sector of Chiqnajota and Tororayoq-Huahuerqa has identified fragments of early ceramics. The archaeological sites of greater importance and than deserve to carry out futures works of archaeological investigation are: Chiqnajota, Raqayniyuq, Kallpa, Llako, Qasamarka, Wallpawiri, Iglesiachayuq, Sillacha, Karpani and Kullkuncha.